Third-Party Logistics Provider Selection for Sustainable Last-Mile Delivery: A Case Study of E-Shop in Belgrade - Švadlenka, Libor; Bošković, Sara; Jovčić, Stefan; Simić, Vladimir; Shashank, Kumar; Zanne, Marina (My University, 2023)
Last-mile delivery (LMD) is one of the crucial phases of the shipping process. Since e-commerce rapidly evolves, there are many issues that should be addressed in city logistics. This paper specifically tackles the issue of Third-Party Logistics (3PL) provider selection for sustainable last-mile delivery. The 3PL selection problem has been solved for the e-shop company from Belgrade, which has online sales. The management of the e-shop company has identified five possible 3PL providers. Those five 3PL providers have been evaluated according to six criteria such as distribution cost, on-time delivery, flexibility of distribution, IT capability, good cultural fit, and customer satisfaction index. To evaluate and rank the 3PL providers, two multi-criteria decision-making methods were coupled. The first one is a Best-Worst Method (BWM) used to find the criteria weights, while the second one is a Combined Compromised Solution (CoCoSo) method utilized to rank the 3PL providers from best to worst one. To check the stability as well as the robustness of the applied methods, sensitivity and comparative analyses are performed. The results show high confidence in the applied methods.
Výběr poskytovatele logistiky třetí strany pro udržitelné dodávky na poslední míli: případová studie e-shopu v Bělehradě
Keywords: Third-Party Logistics; Provider; Selection; Sustainable Last-Mile; Delivery; Case Study; E-Shop; Belgrade; Výběr poskytovatele; logistika třetí strany; udržitelné dodávky; poslední míle; případová studie; e-shop; Bělehrad